A ten gene‐containing genomic island determines flagellin glycosylation: implication for its regulatory role in motility and virulence of Xanthomonas oryzae pv. oryzae. (9th April 2017) - Yu, Chao; Chen, Huamin; Tian, Fang; Yang, Fenghuan; Yuan, Xiaochen; Yang, Ching‐Hong; He, Chenyang
Summary: Flagellin glycosylation plays a crucial role in flagellar assembly, motility and virulence in several pathogenic bacteria. However, little is known about the genetic determinants and biological functions of flagellin glycosylation in Xanthomonas oryzae pv. oryzae ( Xoo ), the causal pathogen of bacterial blight of rice. Here, the structure, regulation and functions of a ten‐gene cluster gigX ( g lycosylation i sland g enes of Xoo ), which was embedded in a flagellar regulon, were characterized. gigX 1 to gigX 10 encoded putative enzymes or proteins involved in glycan biosynthesis and transfer, including a nucleotide sugar transaminase, an acyl‐carrier protein (ACP), a 3‐oxoacyl‐ACP synthase, a 3‐oxoacyl‐ACP reductase, a dehydrogenase, an acetyltransferase, a ring hydroxylating dioxygenase, a hypothetical protein, a methyltransferanse and a glycosyltransferase, respectively. The gigX genes were co‐transcribed in an operon and up‐regulated by the upstream σ 54 factor RpoN2 and transcriptional activator FleQ. In‐frame deletion of each gigX gene affected flagellin glycosylation modification, meaning that the unglycosylated flagellin of the mutants was smaller than the glycosylated flagellin of the wild‐type. No significant changes in flagellar filament and motility were observed in the Δ gigX mutants, among which only Δ gigX 6 displayed increased swimming ability. Importantly, all mutants, except Δ gigX 9, showed significantly increased virulence and bacterial growth in the susceptible rice cultivar IR24, and Δ gigX 1 and Δ gigX 10 showed enhanced type III secretion system (T3SS)‐related gene expression. Moreover, the glycosylated flagellin of the wild‐type induced higher H2 O2 levels in rice leaves than did the unglycosylated flagellins of Δ gigX 1 or Δ gigX 10. Taken together, this study reveals that the gigX cluster determines flagellin glycosylation, and implicates the regulatory role of post‐translational modification with the glycosylation, acetylation and methylation of flagellin in the regulation of motility and virulence of Xoo .